PyramidalExplorer: A new interactive tool to explore morpho-functional relations of pyramidal neurons - Pablo eToharia; Pablo eToharia; Oscar David eRobles Sanchez; Oscar David eRobles Sanchez; Isabel eFernaud; Julia eMakarova; Sergio eGalindo; Angel eRodriguez; Angel eRodriguez; Luis ePastor; Luis ePastor; Oscar eHerreras; et al. (Frontiers Media S.A., 2016)
This work presents PyramidalExplorer, a new tool to interactively explore and reveal the detailed organization of the microanatomy of pyramidal neurons with functionally related models. It consists of a set of functionalities that allow possible regional differences in the pyramidal cell architecture to be interactively discovered by combining quantitative morphological information about the structure of the cell with implemented functional models. The key contribution of this tool is the morpho-functional oriented design that allows the user to navigate within the 3D dataset, filter and perform Content-Based Retrieval operations. As a case study, we present a human pyramidal neuron with over 9000 dendritic spines in its apical and basal dendritic trees. Using PyramidalExplorer, we were able to find unexpected differential morphological attributes of dendritic spines in particular compartments of the neuron, revealing new aspects of the morpho-functional organization of the pyramidal neuron.